Groups whose subnormal subgroups have finite normal oscillation. Issue 9 (2nd September 2017) - Ferrara, Maria; de Giovanni, Francesco
ABSTRACT: If X is a subgroup of a group G, the cardinal numbermin { | X : X G |, | X G : X | } is called the normal oscillation of X in G . The structure of soluble groups in which all subnormal subgroups have finite normal oscillation is investigated here, taking as a model the known theory of T -groups, i.e., groups in which normality is a transitive relation.